Infectious Inequalities Epidemics, Trust, and Social Vulnerabilities in Cinema - Han, Qijun (Taylor & Francis, 2022)
This book explores societal vulnerabilities highlighted within cinema and develops an interpretive framework for understanding the depiction of societal responses to epidemic disease outbreaks across cinematic history. Drawing on a large database of twentieth- and twenty-first-century films depicting epidemics, the study looks into issues including trust, distrust, and mistrust; different epidemic experiences down the lines of expertise, gender, and wealth; and the difficulties in visualizing the invisible pathogen on screen. The authors argue that epidemics have long been presented in cinema as forming a point of cohesion for the communities portrayed, as individuals and groups "from below" represented as characters in these films find solidarity in battling a common enemy of elite institutions and authority figures. Throughout the book, a central question is also posed: "cohesion for whom?", which sheds light on the fortunes of those characters that are excluded from these expressions of collective solidarity. This book is a valuable reference for scholars and students of film studies and visual studies as well as academic and general readers interested in topics of films and history, and disease and society.